Management of a rare case of impacted mandibular second premolar in an unusual position (Indian Journal of Case Reports, 2019)
There is always a high possibility for any tooth to follow a different eruptive path and become impacted within the dentoalveolar process, or other anatomic sites, which include the sinus, mandibular ramus, or inferior border of the mandible. This report describes the case of a 35-year-old male, who was presented with the complaints of pain in the left lower arch for 7 days. On radiographic investigation, it was found that there was a horizontally impacted 2nd premolar in the left mandibular posterior region, positioned below the roots of the 1st and 2nd mandibular molars on the left side inclined distally. Due to the unusual positioning of the tooth and its proximity to the inferior alveolar nerve, the patient was operated extra-orally under general anesthesia for the removal of the impacted tooth.